Mental Health Problems in Chinese Healthcare Workers Exposed to Workplace Violence During the COVID-19 Outbreak: A Cross-Sectional Study Using Propensity Score Matching Analysis - Wang W; Lu L; Kelifa MM; Yu Y; He A; Cao N; Zheng S; Yan W; Yang Y (Dove Medical Press, 2020)
Wei Wang,1,* Lili Lu,2,* Mohammedhamid Mohammedosman Kelifa,3 Yan Yu,3 Anqi He,3 Na Cao,3 Si Zheng,3 Wenjun Yan,1 Yinmei Yang3 1School of Public Health, Xuzhou Medical University, Xuzhou, People’s Republic of China; 2Department of Gastroenterology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China; 3School of Health Sciences, Wuhan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei WangSchool of Public Health, Xuzhou Medical University, Xuzhou, People’s Republic of ChinaTel +86-15152118260Email weiwang90@163.comYinmei YangSchool of Health Sciences, Wuhan University, Wuhan, People’s Republic of ChinaTel +86-15071458786Email yym2015@whu.edu.cnObjective: This study aimed at examining the effect of medical workplace violence (MWV) on the mental health of Chinese healthcare workers during the outbreak of coronavirus disease 2019 (COVID-19).Methods: An anonymous online survey was issued to Chinese healthcare workers (N=1063) from 31 provinces and autonomous regions between February 13th and February 20th. Mental health was measured by the Chinese Depression Anxiety Stress Scales-21 (DASS-21). Medical workplace violence was measured using a single item, whether any type of workplace violence was experienced during the COVID-19 outbreak. Propensity score matching was used to assess the impact of MWV on mental health.Results: Out of 1063, 217 (20.4%) reported experiencing MWV during the COVID-19 outbreak. Before matching, MWV was correlated with elevated mental health problems (b=8.248, p< 0.001), after adjusting for other variables. After matching, Chinese healthcare workers who experienced MWV were more likely to suffer from mental health problems than those who did not.Conclusion: MWV exerts a detrimental effect on mental health among Chinese healthcare workers during the COVID-19 outbreak. It is necessary to create a more supportive and safer work environment for healthcare workers at this special context of the COVID-19 outbreak.Keywords: workplace violence, mental health, COVID-19, propensity score